2009
DOI: 10.1186/1471-2180-9-119
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the Clostridium acetobutylicium FabF and FabZ proteins in unsaturated fatty acid biosynthesis

Abstract: BackgroundThe original anaerobic unsaturated fatty acid biosynthesis pathway proposed by Goldfine and Bloch was based on in vivo labeling studies in Clostridium butyricum ATCC 6015 (now C. beijerinckii) but to date no dedicated unsaturated fatty acid biosynthetic enzyme has been identified in Clostridia. C. acetobutylicium synthesizes the same species of unsaturated fatty acids as E. coli, but lacks all of the known unsaturated fatty acid synthetic genes identified in E. coli and other bacteria. A possible exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Wang and Cronan (35) first showed that one of these proteins, now called FabO, functioned as a KAS I analogous to FabB, whereas the other FabF homologue had KAS II activity. A similar picture was found for the FabF proteins of Clostridium acetobutylicum and Lactococcus lactis (29,41).…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Wang and Cronan (35) first showed that one of these proteins, now called FabO, functioned as a KAS I analogous to FabB, whereas the other FabF homologue had KAS II activity. A similar picture was found for the FabF proteins of Clostridium acetobutylicum and Lactococcus lactis (29,41).…”
supporting
confidence: 60%
“…In contrast, FabF homologues are found throughout the bacteria, and FabF is often considered the generic KAS of long-chain fatty acid synthesis (24,35,41). For several Grampositive bacteria, FabF homologues have been shown to also have KAS I activity (29,35,41). Enterococcus faecalis encodes two FabF homologues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DVU1204 encodes 3-oxoacyl-(acyl-carrierprotein) synthase II FabF (also named as betaketoacyl-ACP synthase II), which has been shown Genetic basis of salt adaptation in D. vulgaris A Zhou et al to function in fatty acid biosynthesis in Synechocystis (Moche et al, 2001) as well as the synthesis of both unsaturated fatty acids and saturated fatty acids in Clostridium (Zhu et al, 2009). The DvH genome lacks unsaturated fatty acids biosynthesis genes fabA and fabB (Campbell and Cronan, 2001); but increased percentages of unsaturated fatty acids have been observed in evolved strains ES9-11 and EC3-10 ( Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few cases indicating that FabF enzymes can play this role have been reported, but they are exclusively in bacteria lacking a homologue of E. coli FabA, including Lactococcus lactis, Enterococcus faecalis, and Clostridium acetobutylicum (12)(13)(14). In this sense, S. oneidensis presents a novel model for FabA-containing bacteria.…”
mentioning
confidence: 99%